Analysis Comparison Advantage of Effort Docking of System Slipway and Docking Lift in Ocean Fishery Port of Nizam Zachman of Jakarta - Herry Boesono; Rahmi Hidayati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2008)
Ocean Fishery Port of Nizam Zachman Jakarta (PPSNZJ) divided into two dock ship, there are dock slipway (governmental property) and dock lift (private sector property). Aim of research is to know technical aspect and finansial aspect and elegibility of effort, to compare economic efficiency and the efficiency seen from earnings and expense and also to know analysis of effort by using statistika test between dock slipway and dock lift. Research used with deskriptif method with items research is technical aspect and finansial aspect of effort dock slipway and dock lift during november till december 2005 with observation method, interview and kuisioner. Result of research concluded that dock slipway use winch to draw ship from sea while dock lift use big krane to lift ship from sea to dock space, considering of finansial aspect that is two dock consider with estimate 10 year forwards that laboured. Analyse efficiency of effort that earning power of dock slipway bigger than dock lift. While efficiency base on earnings and expense, dock slipway is equal to 287,86 % and dock lift is equal to 355 %. Pursuant to statistical test mann-whitney that earnings, expense and advantage per month year 2005 that two dock is no real difference. Keywords : PPSNZJ, technical aspect, aspect of finansial, elegibility of effort